Analysis of the Moisture and Heat Transport in a Wet Porous Sand Layer with Water Sucking Ability. Issue 7 (22nd August 2016) - Chen, Wei; Ling, Juanjuan
Abstract: The moisture content and heat transfer in a wet porous sand layer was influenced by the weather conditions while the layer was exposed outdoors. The changes in water content and temperature in the wet porous bed with water supplied due to the weather conditions differed from the case without water supplied via the bottom in the tests. A one‐dimensional mathematical model describing the heat and mass transfer in the unsaturated porous layer was used to analyze the change of the water content, temperature and rate of water evaporation or vapor condensation in the wet porous layer. As the ambient temperature, relative humidity and solar irradiation changed periodically and the gravity and capillary affected the water transport greatly in the wet porous media, variations of water content and temperature occurred cyclically in the wet porous layer that was exposed to outdoor conditions. In the wet porous bed, the rate of the water evaporation or vapor condensation was closely related to the temperature, gradient of the temperature along the depth and the rate of temperature variation over time. The particle size and porosity associated with the permeability had great impact on the water content and its variation range in the wet porous media with water sucking ability while the weather conditions changed periodically. The simulations of the water content and temperature variation in the sand bed agreed with the test data. All these results can be used to analyze the behavior of heat and moisture in the unsaturated porous layer under weather conditions.